If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + -7(y + 4) = -1y + 6 + -3y Reorder the terms: -3y + -7(4 + y) = -1y + 6 + -3y -3y + (4 * -7 + y * -7) = -1y + 6 + -3y -3y + (-28 + -7y) = -1y + 6 + -3y Reorder the terms: -28 + -3y + -7y = -1y + 6 + -3y Combine like terms: -3y + -7y = -10y -28 + -10y = -1y + 6 + -3y Reorder the terms: -28 + -10y = 6 + -1y + -3y Combine like terms: -1y + -3y = -4y -28 + -10y = 6 + -4y Solving -28 + -10y = 6 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. -28 + -10y + 4y = 6 + -4y + 4y Combine like terms: -10y + 4y = -6y -28 + -6y = 6 + -4y + 4y Combine like terms: -4y + 4y = 0 -28 + -6y = 6 + 0 -28 + -6y = 6 Add '28' to each side of the equation. -28 + 28 + -6y = 6 + 28 Combine like terms: -28 + 28 = 0 0 + -6y = 6 + 28 -6y = 6 + 28 Combine like terms: 6 + 28 = 34 -6y = 34 Divide each side by '-6'. y = -5.666666667 Simplifying y = -5.666666667
| 0=5x^4-150x^2 | | x+3x-26=18 | | 9x-1=50-8x | | 11+9x=43 | | 14x+43-25x=128 | | -7y=x | | 3+65x=52x+12 | | (6x^2-5x+12)+(9x^2+7x-68)= | | 4/7=-12/x | | x-40/x=14 | | 30x=-25-9x^2 | | 6(2x-5)-4=2 | | 2x+6y=2x+3y | | 10-2x=x-10 | | x-40/x=0 | | 3x=-2x+23 | | 2x+6y=2x+6y | | 1/x= | | 3+91x=39x+39 | | -2(7+x)=3(1-2x) | | -5n+1-2n+-4=5 | | 14+3r=56 | | 2x^4-8x^2-42=0 | | -(2a/a-6)=4/a-10 | | 5a-18=27 | | (5zy)(-4z)= | | 32+3x=36 | | 9p-4=77 | | 4x^2+16x=24 | | -5n+1-2n+n-4=5 | | 5x+9+3y+8=180 | | y^2+8y+11=0 |